EGFR gene amplification is relatively common and associates with outcome in intestinal adenocarcinoma of the stomach, gastro-oesophageal junction and distal oesophagus - Birkman E-M; ålgars A; Lintunen M; Ristamäki R; Sundström J; Carpén O (BIOMED CENTRAL LTD, 2022)
BACKGROUND Approximately 50 % of gastric adenocarcinomas belong to a molecular subgroup characterised by chromosomal instability and a strong association with the intestinal histological subtype. This subgroup typically contains alterations in the receptor tyrosine kinase-RAS pathway, for example EGFR or HER2 gene amplifications leading to protein overexpression. In clinical practice, HER2 overexpressing metastatic gastric cancer is known to respond to treatment with anti-HER2 antibodies. By contrast, anti-EGFR antibodies have not been able to provide survival benefit in clinical trials, which, however, have not included patient selection based on the histological subtype or EGFR gene copy number analysis of the tumours. To examine the role of EGFR as a potential biomarker, we studied the prevalence, clinicopathological associations as well as prognostic role of EGFR and HER2 expression and gene amplification in intestinal adenocarcinomas of the stomach, gastro-oesophageal junction and distal oesophagus. METHODS Tissue samples from 220 patients were analysed with EGFR and HER2 immunohistochemistry. Those samples with moderate/strong staining intensity were further analysed with silver in situ hybridization to quantify gene copy numbers. The results were associated with clinical patient characteristics and survival. RESULTS Moderate/strong EGFR protein expression was found in 72/220 (32.7 %) and EGFR gene amplification in 31/220 (14.1 %) of the tumours, while moderate/strong HER2 protein expression was detected in 31/220 (14.1 %) and HER2 gene amplification in 29/220 (13.2 %) of the tumours. EGFR and HER2 genes were co-amplified in eight tumours (3.6 %). EGFR gene amplification was more common in tumours of distal oesophagus/gastro-oesophageal junction/cardia than in those of gastric corpus (p = 0.013). It was associated with shortened time to cancer recurrence (p = 0.026) and cancer specific survival (p = 0.033). CONCLUSIONS EGFR gene amplification is relatively common in intestinal adenocarcinomas and associates with decreased survival. It is rarely concurrent with HER2 gene amplification, suggesting that anti-EGFR therapies might be applicable to some patients not eligible for anti-HER2 treatment. Analogous to HER2 testing, determination of EGFR gene amplification status in concert with immunohistochemistry could improve the specificity of patient selection when investigating the possible benefits of anti-EGFR therapies in the treatment of gastric adenocarcinomas.